2019
DOI: 10.1097/sla.0000000000003461
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Validated Recurrence Risk Score to Guide a Pragmatic Surveillance Strategy After Resection of Pancreatic Neuroendocrine Tumors

Abstract: Objective: Despite heterogeneous biology, similar surveillance schemas are utilized after resection of all pancreatic neuroendocrine tumors (PanNETs). Given concerns regarding excess radiation exposure and financial burden, our aim was to develop a prognostic score for disease recurrence to guide individually tailored surveillance strategies. Methods: All patients with primary nonfunctioning, nonmetastatic well/moderately differentiated PanNETs who underwent curative-intent resection at 9-institutions from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 45 publications
2
45
0
Order By: Relevance
“…Depending on tumor location, size, and proximity to the pancreatic duct, resection may include pancreatoduodenectomy (PD), distal pancreatectomy (DP), or enucleation (EN). In the absence of recurrence, PNETs have a relatively good prognosis compared with other gastrointestinal tumors with a 5‐year survival up to 85% 2‐5 …”
Section: Introductionmentioning
confidence: 99%
“…Depending on tumor location, size, and proximity to the pancreatic duct, resection may include pancreatoduodenectomy (PD), distal pancreatectomy (DP), or enucleation (EN). In the absence of recurrence, PNETs have a relatively good prognosis compared with other gastrointestinal tumors with a 5‐year survival up to 85% 2‐5 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, recent studies have reported poor prognosis in some of the well-differentiated NF-PNETs and factors including tumour grade G2, Ki67 index, lymph node metastasis, perineural invasion and tumour diameter were demonstrated to be associated with recurrence and death. 14,16 However, the European Neuroendocrine Tumor Society guidelines do not recommend adjuvant treatment after surgical resection for these patients 17 and no standard surveillance programmes have been constructed. The results from our data showed that patients with age >52 years and tumour grade G2 were more likely to die after surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hormone clinical syndrome in F-PanNET favors early diagnosis and thus surgical resection at early stages. However, for patients with NF-PanNETs the presence of symptoms at diagnosis is usually related to tumor mass effect or tumoral infiltration on the surrounding structures and therefore is associated with worse prognosis (21,22). To date, because of the recent increased incidental diagnosis of small NF-PanNETs, fewer patients present with symptoms at diagnosis (23).…”
Section: Symptomsmentioning
confidence: 99%
“…Conversely, PNI is a distinct pathologic entity observable in the absence of LVI. The rate of LVI and PNI in PanNETs rages from 22-36% to 17-39%, respectively (9,14,22,32). Vascular and lymphatic vessels and nerves can potentially be a route of metastatic spread to regional lymph nodes and distant organs and are therefore considered a histologic indicator of aggressive tumor behavior.…”
Section: Lymphovascular and Perineural Invasionmentioning
confidence: 99%
See 1 more Smart Citation